2022
DOI: 10.3390/biomedicines10123195
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Microbiome in Connective-Tissue-Associated Interstitial Lung Disease and Pulmonary Vasculitis

Abstract: The microbiome can trigger and maintain immune-mediated diseases and is associated with the severity and prognosis of idiopathic pulmonary fibrosis, which is the prototype of interstitial lung diseases (ILDs). The latter can be a major cause of morbidity and mortality in patients with connective-tissue diseases (CTD). In the present review, we discuss the current evidence regarding microbiome in CTD-ILD and pulmonary vasculitis. In patients with rheumatoid arthritis (RA) the BAL microbiota is significantly les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Previous investigations of the microbiome and idiopathic pulmonary fibrosis have suggested that the microbiome may have an injurious effect on the progression [30,31] and acute exacerbation [32] of diffuse interstitial lung disease. A similar impact was found in connective tissue-associated interstitial lung disease [33]. However, despite several studies on the role of the lung microbiome in the pathophysiology and progression of diffuse interstitial lung disease, there is a paucity of data regarding the impact of fungi on the disease and its natural course.…”
Section: Discussionmentioning
confidence: 59%
“…Previous investigations of the microbiome and idiopathic pulmonary fibrosis have suggested that the microbiome may have an injurious effect on the progression [30,31] and acute exacerbation [32] of diffuse interstitial lung disease. A similar impact was found in connective tissue-associated interstitial lung disease [33]. However, despite several studies on the role of the lung microbiome in the pathophysiology and progression of diffuse interstitial lung disease, there is a paucity of data regarding the impact of fungi on the disease and its natural course.…”
Section: Discussionmentioning
confidence: 59%
“…Shortness of breath, frequently experienced by subjects after recovery from primary SARS-CoV-2 infection, could represent a clinical manifestation of the fibrosis secondary to chronic inflammation of lung parenchyma, leading to reduced total lung capacity. Such a condition is already linked to gut dysbiosis in non-COVID patients, as described in a recent review ( 90 ).…”
Section: Microbiota Dysbiosis In Long-covidmentioning
confidence: 75%
“…It was highlighted that early-onset RA was associated with periodontal diseases. Infections with Prevotella species or P. gingivalis are trigger factors for RA, usually in ACPA-positive patients [ 95 , 96 , 97 ]. The reactions between bacteria and lung parenchyma influence the innate and adaptive immune system and induce autoimmunity via molecular mimicry, bacteria-induced autoantigen production, and immune regulatory reactions [ 98 , 99 , 100 ].…”
Section: Risk Factors For Ra-ildmentioning
confidence: 99%